Importance of pedagogical abilities in estimation by the future teachers of physical culture. - Pechko O.M (Kharkov National Pedagogical University, 2012)
The features of the professional thinking are set for the students of faculty of PE of 3 - 4-th years of studies. Importance of pedagogical abilities is considered in the process of preparation to professional activity of future specialists on a physical culture. Taking into account importance of problem of forming of the professional thinking of future teachers of physical culture a study on finding out of priority of pedagogical abilities was undertaken in the estimation of students of faculty of PE. The amount of investigated presented 216 persons of III and IV courses of physical education faculty. For evaluation it was proposed 20 most necessary pedagogical abilities. The indexes importance of ranking of professional abilities is set for the students of faculty of PE. It is also educed that depending on the year of studies of students, priority in the choice of importance of pedagogical abilities are examined both in identical aspects and on anything.